2021
DOI: 10.3390/ma14247564
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of Pyrolysis and Thermo-Oxidative Decomposition of Tennis String Nylon Wastes

Abstract: Thermal degradation of nylon-6 tennis string nylon wastes in inert nitrogen and air atmospheres was investigated by means of multiple heating-rate thermogravimetric analyses. The results obtained under the heating rates of 5–20 K/min are compared in terms of degradation feature and specific temperature for two atmospheres. Using nonisothermal data, kinetic analysis was thoroughly conducted using various isoconversional model-free methods, including Starink, Madhusudanan–Krishnan–Ninan, Tang, Coats–Redfern, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…Singh et al (2021) [ 20 ] found the mechanism reaction of the third-order reaction (F3), diffusion Jander (D3), and Ginstling–Brounshtein (D4) models to be best suited for CC pyrolysis, PE pyrolysis, and co-pyrolysis, respectively. Wan and Huang (2021) [ 34 ] used the master plot to obtain the first-order reaction model (D1), which was the most suitable mechanism function for describing the pyrolysis of nylon-6 waste.…”
Section: Resultsmentioning
confidence: 99%
“…Singh et al (2021) [ 20 ] found the mechanism reaction of the third-order reaction (F3), diffusion Jander (D3), and Ginstling–Brounshtein (D4) models to be best suited for CC pyrolysis, PE pyrolysis, and co-pyrolysis, respectively. Wan and Huang (2021) [ 34 ] used the master plot to obtain the first-order reaction model (D1), which was the most suitable mechanism function for describing the pyrolysis of nylon-6 waste.…”
Section: Resultsmentioning
confidence: 99%
“…It should be highlighted here that the temperature-integral function in the right-hand side of Equation (7) has no analytical solution and it might be solved numerically or approximated to different extents. As for the reaction mechanism functions available either in differential f ( a ) or in integral g ( a ), some literature can be referred to for the details [ 7 , 8 , 28 ].…”
Section: Materials and Analysis Methodsmentioning
confidence: 99%
“…Thereafter, the model-fitting efforts are made by plotting Y n against E kn over 0.05 < α < 0.95 for all g ( α ) models [ 7 , 8 , 28 ]. For simplicity, one global reaction model is assumed herein for the entire kinetic degradation process.…”
Section: Materials and Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, as the demand for chemical processes and the maturity of experimental techniques for thermal analysis have increased, this method has commonly been applied to evaluate the thermal stability of organics, inorganics, and polymers. Thermodynamic analysis is mainly used to obtain the "kinetic triple factors" (pre-exponential factor (A), activation energy (E a ), and reaction mechanism function) of a reaction by means of established mechanism functions [17][18][19].…”
Section: Thermodynamic Analysismentioning
confidence: 99%